Contribution to the study of Chagas disease epidemiology in three southern Peru localities - Solís, Hilda (2003)
Objectives: To determine the presence of IgG anti-Trypanosoma cruzi antibodies in humans and the triatomines feeding habits in 3 Nasca, Peru provinces housings. Material and methods: IgG anti-T. cruzi antibodies were studied by RIFI and ELISA methods in 867 inhabitants blood samples (excluding less than one year-old children) in Tulin, Vista Alegre and Changuillo localities in order to determine Chagas disease. We also investigated 494 houses conditions, captured 581 samples of Triatoma infestans (411 nymphs and 170 adults) and intestinal contents were studied for feeding habits and search for T. cruzi. Results:We identified IgG anti-T. cruzi antibodies in 128 inhabitants samples (14,8%), 89 (15,9%) females and 39 (12,6%) males. Precipitine reaction in capillary tube (8 antigens) identified feeding origin in 401 insects (69,0%), mainly birds 252 (43,4%), rodents 36 (6,2%), humans 23 (3,9%) and dogs (1,6%). One T. infestans female was found infected with T. cruzi. Conclusions: Human positivity of Trypanosoma cruzi antibodies was 14,8% and human blood ingestion was found in 3,9% of triatomines, representing a risk factor for Chagas disease.